Influence of motivation on rehabilitation outcomes after subacute stroke in convalescent rehabilitation wards - Yoshida, Taiki; Otaka, Yohei; Kitamura, Shin; Ushizawa, Kazuki; Kumagai, Masashi; Yaeda, Jun; Osu, Rieko (Frontiers in Neurology, 2023)
BACKGROUND: The motivation for rehabilitation is important in encouraging stroke patients to participate in rehabilitation; however, its relationship with outcomes is not well known. In addition, changes in patient motivation during hospitalization have not been examined. AIM: To examine the relationship between motivation and rehabilitation outcomes for subacute stroke patients and to investigate the changes in motivation. DESIGN: Prospective cohort study. SETTING: Subacute rehabilitation hospital. POPULATION: The study enrolled a consecutive sample of patients (N=201) with stroke admitted to a subacute rehabilitation ward from October 2017 to March 2019. METHODS: The functional independence measure and motivation in stroke patients for rehabilitation scale was evaluated at admission; at one, two, and three months after admission; and at discharge. The effectiveness and efficiency of the functional independence measure were calculated as rehabilitation outcomes. The effect of motivation on outcomes and the change in motivation in stroke patients for rehabilitation scale scores over time were analyzed using a linear mixed model. RESULTS: The median (interquartile range) converted motivation in stroke patients for rehabilitation scale scores (converted to a range of 0–100) at admission; one, two, and three months after admission; and discharge was 86 (76–95), 83 (77–94), 81 (74–95), 81 (71–93), and 84 (75–95), respectively. The median (interquartile range) of effectiveness and efficiency of the functional independence measure from admission to discharge was 0.82 (0.68–0.91) and 0.41 (0.30–0.59), respectively. Motivation in stroke patients for rehabilitation scale scores were not significantly associated with the effectiveness and efficiency of the functional independence measure (P>0.05). Motivation in stroke patients for rehabilitation scale scores were significantly lower at two (β=-3.1, 95% confidence interval [-5.3, -0.9], P=0.005) and three (β=-4.4, 95% confidence interval [-7.3, -1.6], P=0.002) months after admission than at admission. CONCLUSIONS: Motivation might not directly affect rehabilitation outcomes assessed by the functional independence measure. Furthermore, many participants remained highly motivated, although their motivation decreased at two or three months after admission. CLINICAL REHABILITATION IMPACT: Assumptions that rehabilitation is ineffective because of low motivation may not be correct. To examine the influence on outcomes, both motivation and daily activities should be considered.